2021
DOI: 10.1021/acs.analchem.1c02913
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Band Gaps of Semiconductors by Cataluminescence

Abstract: A rapid and efficient methodology for the evaluation of band gaps of semiconductors is highly desirable to analyze and assess the intrinsic properties and extending application scopes of semiconductor materials. Here, the negative correlation of the cataluminescence (CTL) signal in the presence of H2S and the band gap of Aurivillius-type perovskite oxide Bi4+n Fe n Ti3O12+3n (n = 1–4) was confirmed, where the H2S-induced CTL signal acts as a probe to evaluate the band gaps of semiconductor materials. The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This phenomenon can be explained that the radius of the Cr 3+ ion (0.615 Å) was smaller than that of the Ga 3+ ion (0.62 Å) by the Bragg equation, indicating the successful doping of Cr 3+ . 32 As shown in the Figure 1b and Figure S3, the XPS results of the representative samples revealed three kinds of peaks at both 1044.2 and 1021.2 eV (Zn 2p), at both 1144.3 and 1117.4 eV (Ga 2p), and at both 585.6 and 576.0 eV (Cr 2p peaks). Importantly, the TEM images showed excellent dispersibility and uniform morphology with 9 nm of ZGC-3 NPs (Figure 1c), indicating great potentials for further reliably sensing nanoplatforms.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…This phenomenon can be explained that the radius of the Cr 3+ ion (0.615 Å) was smaller than that of the Ga 3+ ion (0.62 Å) by the Bragg equation, indicating the successful doping of Cr 3+ . 32 As shown in the Figure 1b and Figure S3, the XPS results of the representative samples revealed three kinds of peaks at both 1044.2 and 1021.2 eV (Zn 2p), at both 1144.3 and 1117.4 eV (Ga 2p), and at both 585.6 and 576.0 eV (Cr 2p peaks). Importantly, the TEM images showed excellent dispersibility and uniform morphology with 9 nm of ZGC-3 NPs (Figure 1c), indicating great potentials for further reliably sensing nanoplatforms.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…Besides, our previous work 15 has demonstrated that there is significant negative correlation between CTL reaction and BTO after excluding the effect of the properties of the material surface.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…Besides, our previous work has demonstrated that there is significant negative correlation between CTL reaction and energy band gap of the semiconductor catalyst, which is due to the more active electron transfer ability of narrow band gap materials under the same thermal excitation conditions, accelerating the catalytic oxidation process. Thus, it is necessary to further investigate the electronic structure of the materials that may influence catalytic efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations